1998
DOI: 10.1021/jo980970t
|View full text |Cite
|
Sign up to set email alerts
|

1-Alkenesulfinyl Chlorides:  Synthesis, Characterization, and Some Substitution Reactions

Abstract: A number of 1-alkenyl sulfoxides bearing either a diphenylmethyl (DPM) or a p-methoxybenzyl (PMB) group have been prepared and exposed to the chlorine surrogate SO2Cl2. Through an oxidative fragmentation reaction, a new family of sulfur acid derivatives, 1-alkenesulfinyl chlorides, is generated. They can be characterized by IR spectroscopy before chemical capture with an alcohol. Ethenesulfinyl chloride (2a) and 1-propenesulfinyl chloride (2b), obtained from their corresponding DPM precursor, can be distilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…[17] It was reported that p-methoxybenzyl and diphenylmethyl groups could be oxidatively cleaved from the sulfinyl unit, offering a collection of monosubstituted ethenesulfinic acid derivatives. As discovered above, the 2-(trimethylsilyl)ethyl functionality also promotes fragmentation and, accordingly, a number of sulfoxides were prepared for evaluation as precursors to sulfinyl chlorides.…”
Section: -Alkenesulfinyl Chloridesmentioning
confidence: 99%
See 4 more Smart Citations
“…[17] It was reported that p-methoxybenzyl and diphenylmethyl groups could be oxidatively cleaved from the sulfinyl unit, offering a collection of monosubstituted ethenesulfinic acid derivatives. As discovered above, the 2-(trimethylsilyl)ethyl functionality also promotes fragmentation and, accordingly, a number of sulfoxides were prepared for evaluation as precursors to sulfinyl chlorides.…”
Section: -Alkenesulfinyl Chloridesmentioning
confidence: 99%
“…Depending on the substrate(s) chosen, there is adequate opportunity to create highly substituted ethenesulfinyl entities, thereby fashioning a protocol that is complementary to the existing 1-alkenesulfinyl chloride preparation. [17] Scheme 3 Scheme 3 shows several reaction equations outlining the synthesis of the starting materials prepared for this section of the study. The addition of 2-(trimethylsilyl)ethanesulfenyl chloride (5) across the double bond of cyclopentene and dihydropyran afforded the expected β-chlorosulfide adducts, which were treated with base to eliminate readily HCl and create, after oxidation, sulfoxides 6.…”
Section: -Alkenesulfinyl Chloridesmentioning
confidence: 99%
See 3 more Smart Citations